ANALYSIS OF CHANGES IN MANGROVE AREA AND SEDIMENTATION ON THE INDAH KAPUK BEACH USING REMOTE SENSING DATA - Zakiyah, Umi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2020)
Currently the construction of reclamation in Jakarta Bay being carried out on several islands that have been approved by the Government of Indonesia and located nearby the Mangroves forests ecosystem which always inundated by seawater and are affected by tides. The purpose of this study were analyzing the changes in the mangrove ecosystem area due to the changes in Total Suspended Solid (TSS) based sedimentation and the effect of hydro-oceanography factors on the TSS. This research was conducted using a literature study, processing the LANDSAT OLI images for the analysis of mangrove changes, TSS analysis, and analysis of the effect of hydro-oceanography on TSS within the years of 2013 to 2020. The results of this study indicate that the area of mangrove forest on the coast of North Jakarta is enlarging by 3-5 ha/year, especially in the reclamation island area due to the process of sedimentation which is influenced by hydrooceanography. High sedimentation can be shown from the high value of Total Suspended Solid (TSS) in the waters. The TSS values processed by the satellites images also showed a significant increase during these years between 2013 to 2020 except December 2018 experienced the lowest value. While the hydro-oceanographic factor has lesser effect on the TSS value compare to mangrove ecosystem in the study area.